2013
DOI: 10.1177/0002764213487341
|View full text |Cite
|
Sign up to set email alerts
|

Racism and Health II

Abstract: This article reviews the empirical evidence that suggests that there is a solid foundation for more systematic research attention to the ways in which interventions that seek to reduce the multiple dimensions of racism can improve health and reduce disparities in health. First, research reveals that policies and procedures that seek to reduce institutional racism by improving neighborhood and educational quality and enhancing access to additional income, employment opportunities and other desirable resources c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(61 citation statements)
references
References 117 publications
2
59
0
Order By: Relevance
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with several reviews and studies that have consistently suggested that experienced discrimination has a harmful psychological impact on those against whom it is directed (e.g., Brondolo et al, 2009b;Harrell, 2000;Harris et al, 2006: Krieger, 1999Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Discussionsupporting
confidence: 90%
“…Numerous review articles have found that racial/ethnic discrimination contributes to variations in health risks within racial and ethnic minorities (Brondolo, Gallo, & Myers, 2009b;Paradies, 2006;Priest et al, 2012;Williams & Mohammed, 2009;2013a;2013b).…”
Section: Racial/ethnic Discrimination and Psychological Well-beingmentioning
confidence: 99%
“…Health disparities based on age, gender, race, ethnicity, religion, ability, socioeconomic status, and sexual orientation occur within a broad social context and have an adverse effect on public health and health care delivery (Williams & Mohammed, 2013). The Institute of Medicine (IOM) (2010) cites that biases, stereotyping, and communication barriers, in addition to other factors, are contributing to health disparities within the US.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But simply observing that a disparity exists does not tell us how to reduce it or what certain interventions might achieve. To make progress, we move from counterfactual thinking to counterfactual methods that conceptualize a finer model where a disparity in some outcome (e.g., wages) is perpetuated by disparities in, or the differential effects of, manipulable determinants of that outcome (e.g., educational attainment) [11,[23][24][25]. With counterfactual methods, we examine the extent to which an intervention on that determinant might reduce disparities (as in observational data) [26] or actually does so (as in a trial) [27,28].…”
Section: Counterfactual Thinking and Intersectionalitymentioning
confidence: 99%